Estimation scheme for parameters of wireless channel model in OFDM communication systems - WANG Yong; GE Jian-hua; WU Xiao-li (Tongxin xuebao)
The conventional channel estimator in OFDM system was designed to cope with the worst-case channel condi-tion,thus performance degradation can be induced due to the imperfect channel estimation.Though wiener filter based on the minimum mean-squared error（MMSE） is the optimal linear estimator,it requires the prior information of transmis-sion channel.In order to select the near optimal prestored channel interpolation filter coefficients,three channel parame-ters detecting methods including maximum multipath delay,Doppler frequency and SNR based on the time and fre-quency correlation functions of the channel,the Euclidean distance of hard-decision in pilots position respectively,were proposed.The method proposed with low complexity allows an efficient implementation for adaptive channel estimation algorithm as well as multi-user OFDM systems.